PENGARUH FUNGSI KEPEMIMPINAN DAN KEPUASAN KERJA TERHADAP KINERJA PRAJURIT MELALUI BUDAYA ORGANISASI - Fadhlon Fadhlon; Nur Halima; Sayekti Suindyah Dwiningwarni (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2023)
The reseach aims to determine the Effect of Leadership Functions and Job Satisfaction on Soldier Performance Through Organizational Culture (Study on KRI Keris-624 Surabaya). This type of research is explanatory research, and the approach is quantitative. The sampling method used in this research is saturated sampling. Data analysis technique using PLS.Version.3.0. The results of the study show that the Leadership Function has a significant effect on the KRI Keris-624 Soldier's Performance. Organizational Culture significantly influences KRI Keris-624 Soldier Performance. Job Satisfaction has a significant effect on KRI Keris-624 Soldier Performance. The Leadership Function through Organizational Culture has a significant effect on the Performance of KRI Keris-624 Soldiers. The Leadership Function through Job Satisfaction has a significant effect on the KRI Keris-624 Soldier's Performance. The leadership function has a significant effect on organizational culture at KRI Keris-624. The Leadership function has a significant effect on Soldier Job Satisfaction in KRI Keris-624.